EFEKTIFKAH PELAYANAN IZIN USAHA ONLINE SINGLE SUBMISSION? STUDI KASUS PADA DPMPTSP KOTA DEPOK PROVINSI JAWA BARAT - Mutia Nabella Sentosa; Andi Masrich (Ensiklopedia of Journal, 2023)
This qualitative research aims to reveal how the to determine the effectiveness of the Online Single Submission business license service with a case study at DPMPTSP Depok City, West Java Province. Measuring effectiveness is generally used with the following methods: 1) program success; (2) target success; (3) satisfaction with the program; and (4) achievement of overall goals. Data collection techniques used are interviews and documents. The informants in this study are policy implementers and target groups. Based on the results of the study it was concluded that the Online Single Submission business license service at DPMPTSP Depok City, West Java Province is said to be quite effective, although there are still obstacles in the implementation of this service. The obstacle faced by the Depok City DPMPTSP in this service is that there are still business actors who manage this permit through a service bureau which is the cause of the OSS system in Depok City not being fully effective.